-2+x-4x=11

Simple and best practice solution for -2+x-4x=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+x-4x=11 equation:


Simplifying
-2 + x + -4x = 11

Combine like terms: x + -4x = -3x
-2 + -3x = 11

Solving
-2 + -3x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -3x = 11 + 2

Combine like terms: -2 + 2 = 0
0 + -3x = 11 + 2
-3x = 11 + 2

Combine like terms: 11 + 2 = 13
-3x = 13

Divide each side by '-3'.
x = -4.333333333

Simplifying
x = -4.333333333

See similar equations:

| 5(6)+3(7)= | | -4+3x=-12+25xfraction | | 2y-4*0=10 | | x-2 = 9 (4-10x)4 | | 9y-5y-9=48.80 | | W-8=23 | | 2y+-4*-2=10 | | -42=-6(z-3) | | 5x+9=82-8x | | -3k^2g-[4kg^2-(6k^2g-2kg^2)]=0 | | 3x-3y+3=2 | | Log(3t+1)=5 | | 49=17(t+1) | | 14abc-[3ab^2c+(4a^2bc)-(-3ab^2c-5abc+5a^2bc)]=0 | | -3y+3=2 | | 3.8=m+9.7 | | -3y+3=0 | | 14abc-[3ab^2+(4a^2bc)-(-3ab^2c-5abc+5a^2bc)]=0 | | -3y-3=0 | | E-5=-13 | | 2-s=9 | | 9x^3-729=0 | | 5x-15+3x=5+8x-20 | | 4n^2-4n=0 | | 5(3x-3)+5x=6x+25-x | | x^2-11x-432=0 | | 9x+5=-3x+5+12x | | 3x+1=3x+9 | | S+9=13 | | 8u=-96 | | 3x^2-2xy=8y | | (4m^3-10m^2+2m+3)+(5m^3+3m^2-4m-7)=0 |

Equations solver categories